Welfare reforms and cild well-being in the US and UK - Jane Waldfogel (Institute for Labour Market Policy Evaluation (IFAU), 2008)
This paper examines the effects of recent welfare reforms in the US and UK on the well-being of children in low-income families, looking specifically at the effects on poverty, family expenditures, and child health and development. The paper finds some commonalities but also some notable differences. Common to both countries is a sizable reduction in child poverty, although the reduction in child poverty in the US has been less, and some families appear to have been left behind. Expenditure data also point to divergence across the two countries. In the UK, low-income families affected by the reforms are spending more money on items related to children and are more likely to own a car and a phone, while in the US, families affected by welfare reforms are primarily spending more money on items related to employment but not items for children. Finally, a common finding across countries is a relative dearth of more direct evidence on the well-being of children, and specifically how the reforms have affected child health and development. Identifying such effects remains an important topic for further research.
Keywords: I3; J1; 330; Welfare reform; Child well-being; Sozialreform; Kinder; Soziale Lage; Armut; Öffentliche Sozialausgaben; Vergleich; USA; Großbritannien